Heavy Metal Uptake by Aptenia cordifolia as Utility for Sewage Sludge Compost Recuperation using Leachate - ZAIMOGLU, ZEYNEP; ERDOGAN, REYHAN; KEKEC, SECIL; YAVUZ SUCU, M.; BUDAK, FUAT (Asian Journal of Chemistry, 2010)
In this study, the use of composted sewage sludge as a binary component with tuff in growth media for a horticultural crop, Aptenia cordifolia was evaluated. Pot experiments were conducted using three different test media: First medium, the SS-W, consists of 50 % sewage sludge compost and 50 % tuff and tap water was used for its irrigation; the same medium was used in the second test, the SS-L, except leachate was used for the irrigation; the remaining test medium consisted of 100 % tuff, the Tuff-W and tap water for irrigation. Each treatment was composed of four repetitions. Plant growth and accumulation of Zn, Pb, Cd, Cr, Ni contents in plants roots and stems were determined. At the end of the study, heavy metal accumulation was highest with the test medium SS-L, which had sewage sludge compost as media and irrigated with leachate. Accumulation on the roots of A. cordifolia plant was higher compared to the stem. In conclusion, the use of sewage sludge compost and leachate irrigation is the most efficient test medium for heavy metal uptake by the plant A. cordifolia at raised levels of Zn, Pb, Cd, Cr, Ni and thus can be used as a cost-effective solution for recuperation of the soil from the heavy metal pollution.